Cooperative transmission design combining network coding and superposition coding - Hai-rong WANG; Yong-ming HUANG; Lv-xi YANG (Tongxin xuebao)
A joint network coding (NC) and superposition coding scheme was proposed to realize a cooperative transmission.The use of NC was able to improve spectral efficiency over classical decode and forward relaying strategy by relaxing the orthogonality constraint between different data streams and mitigating the resultant interference through precoding.In contrast to using the CSI based beamforming scheme which could achieve near optimal performance but involves huge computational complexity,designing the beamforming vector using the form of superposition coding was proposed,such that CSI at the transmitters were not required and the involved computation was greatly reduced.The theoretical analysis and simulation results reveal that the proposed scheme shows performances close to the near-optimal CSIT based scheme.